State of immune status in hematological patients with invasive aspergillosis - E. V. Frolova; O. V. Shadrivova; L. V. Filippova; A. E. Uchevatkina; A. G. Volkova; M. O. Popova; L. S. Zubarovskaya; I. S. Zjuzgin; T. S. Bogomolova; N. V. Vasilyeva; B. V. Afanasyev; N. N. Klimko (Журнал инфектологии)
Invasive aspergillosis – is severe mycotic infection that often occurs in hematological patients and is characterized by high mortality. We examined the immunological parameters of hematological patients with invasive aspergillosis developed after cytostatic chemotherapy. Was founded, disruption of all parts of the immune respons: reduction in the absolute number of T-helper cells (CD4 +), natural killer cells (CD16 +), lowering of IFN-γ and IL-10 production, reduction in the number of B-lymphocytes and immunoglobulin levels of all classes, suppression killer ability of neutrophils are features of immune status in hematological patients with invasive aspergillosis receiving cytostatic chemotherapy.